Influence of Soil Liquefaction on the Structural Performance of Bridges During Earthquakes: Showa Bridge as A Case Study - K. Dhahir, Mohammed; Nadir, Wissam; H. Rasool, Mohammed (International Journal of Engineering and Technology, 2018)
Liquefaction is generally defined as the loss of contact between soil particles during shaking (earthquakes), and it usually occurs in saturated loose sandy soils where the timescale is insufficient for the water to drain from the pores, thus increasing the excess pore pressure, and thereby floating the sand particles. For regular structures with shallow foundations, liquefaction normally leads to loss of soil strength, which leads to settlement of foundations. On the other hand, bridges are usually supported with piles foundation, which introduces additional effects during liquefaction. Therefore, this paper examines the possible effects of liquefaction on the structural performance of bridges during earthquakes. Furthermore, the failure of Showa Bridge during the 1964 Nagata earthquake was also discussed and analyzed as an example of the catastrophic effects of liquefaction. The analysis shows that the most influential effect during liquefaction is the increase in the unsupported length of piles, which leads to several adverse effects such as increasing the lateral displacement, reduce the buckling capacity, increase the bending moment, and reduce the shaft capacity of the pile. Finally, recommendations regarding the design of pile supported bridges in seismic areas with liquefiable soils have also been suggested.Â